2013
DOI: 10.1111/1365-2745.12074
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients as natural laboratories to infer species' responses to temperature

Abstract: Summary1. Macroclimatic variation along latitudinal gradients provides an excellent natural laboratory to investigate the role of temperature and the potential impacts of climate warming on terrestrial organisms. 2. Here, we review the use of latitudinal gradients for ecological climate change research, in comparison with altitudinal gradients and experimental warming, and illustrate their use and caveats with a meta-analysis of latitudinal intraspecific variation in important life-history traits of vascular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
365
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(390 citation statements)
references
References 133 publications
22
365
2
1
Order By: Relevance
“…For most plants, height plays an important role in their competitive ability [25,26]. Previous studies showed that plant height decreases with increasing latitude [25], but significantly increases with increasing temperature [27]. The present results indicated that the height of C. canadensis decreased with increasing latitude except Xiamen, which featured a subtropical marine climate.…”
Section: Discussionsupporting
confidence: 47%
“…For most plants, height plays an important role in their competitive ability [25,26]. Previous studies showed that plant height decreases with increasing latitude [25], but significantly increases with increasing temperature [27]. The present results indicated that the height of C. canadensis decreased with increasing latitude except Xiamen, which featured a subtropical marine climate.…”
Section: Discussionsupporting
confidence: 47%
“…The south-north and oceanic-continental gradients are important factors that influence the vegetation composition through, for example, variation in temperature and precipitation (Nilsen & Moen 2009;De Frenne et al 2013). A continuous model for regional environmental variation in Norway has been developed by Bakkestuen et al (2008).…”
Section: Environmental Datamentioning
confidence: 99%
“…This strategy reflects the behavior of many relevant phenomena in nature, where individuals move towards a major concentration or a greater measure of some element. For example, animals perform migratory tasks by leveraging environmental cues such as nutrient [42] and thermal gradients [43], or magnetic fields [44]. Even at a cellular level, there is a reaction that triggers lymphocyte chemotaxis towards the tumor to form a lymphocyte barrier to contain tumor progression [45].…”
Section: Gradientmentioning
confidence: 99%